Penerapan Metode LBS Menentukan Lokasi Coffee Shop Pada Dinas Ekonomi Kreatif Provinsi Papua - Ramadhan, Tsany Rafi; Tatuhey, Emy Lenora (STMIK Banjarbaru, 2024)
Searching for coffee shops in Jayapura City via Google Maps encountered problems due to inaccurate and incomplete data. The data on Google Maps does not match the data from the Papua Province Creative Economy Service, mixes up various types of coffee drinking places, and is not verified so it is easy to change and is detrimental to coffee shop owners. This causes difficulties for tourists, out-of-town service employees and local residents in finding a coffee shop that suits their needs. This research aims to implement a system with Location Based Service to provide accurate, complete and verified coffee shop information in Jayapura City. The results of black box testing state that the LBS system for determining coffee shop locations in Jayapura City provides an effective and efficient solution for the Creative Economy Service.Keywords: Location based service; Coffee shop; Jayapura AbstrakPencarian coffee shop di Kota Jayapura melalui Google Maps menemui kendala karena data yang tidak akurat dan tidak lengkap. Data di Google Maps tidak sesuai dengan data Dinas Ekonomi Kreatif Provinsi Papua, mencampurkan berbagai jenis tempat minum kopi, dan tidak diverifikasi sehingga mudah diubah dan merugikan pemilik coffee shop. Hal ini menyebabkan kesulitan bagi wisatawan, pegawai dinas luar kota, dan warga lokal dalam menemukan coffee shop yang sesuai kebutuhan. Penelitian ini bertujuan untuk menerapkan sistem dengan Location Based Service untuk memberikan menyediakan informasi coffee shop yang akurat, lengkap, dan terverifikasi di Kota Jayapura. Hasil dari pengujian blackbox menyatakan bahwa bahwa sistem dengan LBS dalam menentukan lokasi coffee shop di Kota Jayapura memberikan solusi yang efektif dan efisien bagi Dinas Ekonomi Kreatif.